LATEST STRATEGIES IN IMPROVING THE QUALITY OF EDUCATION AT SCHOOL - Babun, Babun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to describe: 1) the madrasa head's strategy in improving the quality of education at Ar-Rofi'iyyah Islamic Middle School; 2) supporting and inhibiting factors in improving the quality of education at Ar-Rofi'iyyah Islamic Middle School. 3) the impact of implementing the madrasah supervisory strategy on improving the quality of education at Ar-Rofi'iyyah Islamic Middle School. This research is qualitative research, where data is collected through interviews, observations and document studies. The collected data was analyzed through data reduction, data display and data verification processes. The research results show: 1) the principal's strategy in improving the quality of education can be seen in the school's vision and policies that are qualityoriented, exploring student competencies, developing teacher competencies, and establishing partnerships; 2) supporting factors in improving the quality of education are the leadership of school principals who focus on quality and community support. Meanwhile, the inhibiting factor is that quality awareness is not evenly distributed among all school members; 3) The principal's strategy has an impact on increasing the recognition of Ar-Rofi'iyyah Islamic Middle School by the community, increasing graduation rates, increasing work partners, improving the development of students' interests and talents, and increasing teacher competence.